Optimization of Liquid Culture Condition of a Novel Fungus Hygrophoropsis sp. and Antioxidant Activity of Extracts - Liang Huang; Chunxia Li; Ning Sun; Yu Wang; Hongpeng Yang; Yiting Li; Litong Ban (Biochemistry Research International)
To evaluate pharmacological activities of a novel fungus Hygrophoropsis sp., the influence of aeration rate on the production of mycelial biomass, exopolysaccharides (EPS), and intrapolysaccharides (IPS) in the fungus Hygrophoropsis sp. was investigated. And the water extracts of cultured Hygrophoropsis sp. mycelia and the fermentation broth were analyzed for their antioxidation activity by using four different assay methods such as hydroxyl radical scavenging, superoxide radical scavenging, hydrogen peroxide scavenging, and reducing power. The Hygrophoropsis sp. was cultivated under various aeration rates in a 7 l bioreactor. The highest mycelial biomass (3.98 mg/mL) and IPS production (19.63 mg/g) were obtained at aeration rate 4.5 v.v.m. The results showed that Hygrophoropsis sp., in general, possesses a strong antioxidation activity in all assays tested. The deproteinized extracts had stronger antioxidation activity as compared to the un-deproteinized extracts by using superoxide radical scavenging, hydrogen peroxide scavenging, and reducing power. Besides, the un-deproteinized extracts had stronger antioxidation activity as compared to the deproteinized extracts by using hydroxyl radical scavenging. Thus, the polysaccharide extractions from the Hygrophoropsis sp. studied have antioxidant activities in vitro, which may be a good source of natural antioxidants or further investigation as potential natural antioxidants.